EFFECTIVENESS OF HIGH INTENSITY INTERVAL TRAINING (HIIT) IN IMPROVING CARDIOVASCULAR FITNESS IN YOUNG ADULTS - Suriah Hanafi; Ikadarny, Ikadarny (International Journal of Teaching and Learning, 2024)
High Intensity Interval Training (HIIT) has gained widespread attention as a method for improving cardiovascular fitness. This study aims to review existing literature regarding the effectiveness of HIIT in improving cardiovascular fitness in young adults. This literature research involved the collection and analysis of articles published in various scientific journals from 2010 to 2023. The keywords used in the search were "High-Intensity Interval Training", "cardiovascular fitness", and "young adults". Inclusion criteria included studies measuring the impact of HIIT on VO2 max and other cardiovascular parameters in healthy young adult subjects. Literature analysis shows that HIIT can significantly increase VO2 max in young adults, an important indicator of cardiovascular fitness. This increase is supported by physiological changes that occur in the body, including increased mitochondrial capacity and oxygen use efficiency. Studies also show improvements in cardiovascular parameters such as blood pressure and lipid profile. HIIT is an effective exercise method for improving cardiovascular fitness in young adults. The significant advantage of HIIT lies in its short workout duration yet providing optimal results, making it an attractive option for individuals with limited time. However, more research is needed to examine the long-term effects and more detailed physiological adaptations to HIIT in a broader population.